Mathematical formulation of energy efficient routing with constraint in mobile ad hoc network - Sahu, Rakesh; Chaudhari, Narendra (International Journal of Engineering and Technology, 2018)
Energy consumption of nodes during the transmission is an important factor for the efficiency and lifetime of a mobile ad hoc network. The reduction in consumption of energy can be achieved, only when its consumption at each step is known. The purpose of this paper is to formulate the mathematical model of energy consumption of network on the basis on links and available nodes in order to formulate the energy optimization function. The probability of link failure in route and innetwork have been taken into consideration as constraints while formulating the objective function of estimated energy consumption, as the low connectivity is one of the challenges due to mobility in ad hoc network.